1997
DOI: 10.1097/00000658-199707000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amylase Level on Admission in the Diagnosis of Blunt Injury to the Pancreas

Abstract: To avoid failure in the detection of pancreatic injury, the authors advocate determination of serum amylase levels more than 3 hours after trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(67 citation statements)
references
References 18 publications
4
58
1
4
Order By: Relevance
“…There are limitations regarding the use of serum amylase to diagnose pancreatic trauma because it can be negative in early stages of less than 3 hours after the injury 22 . Furthermore, it may be raised without serious abdominal injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limitations regarding the use of serum amylase to diagnose pancreatic trauma because it can be negative in early stages of less than 3 hours after the injury 22 . Furthermore, it may be raised without serious abdominal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our second patient presented after 24 hours of the injury. The most important factor that affects the serum amylase level on admission is the elapsed time from injury to admission 22 . About 70% of the patients who have pancreatic injuries will have raised serum amylase on admission 3,23 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Serial or delayed serum amylase levels have been more useful. 10 Helical contrast-enhanced CT scan is the initial imaging study of choice for detection of pancreatic injury in a stable patient. Reported sensitivity and specificity rates are as high as 90%, Some of the CT findings suggestive of pancreatic injuries include peri-pancreatic fluid in the lesser sac; pancreatic hematoma or laceration and focal edema at the site of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…The limits of this examination in defining the presence and gravity of pancreas trauma are well known. It was reported that the sensitivity of pancreatic rupture is 42.9% [6,10,11] and its low accuracy is particularly critical in defining the damage of the main pancreatic duct, the single most important factor both for surgical indication and choice of the best surgical strategy [12][13][14] . In our case, CT allowed to exclude thoracic lesions and to focus on the pancreatic region, demonstrating the pancreatic body fracture and the presence of associated vascular damage.…”
Section: Discussionmentioning
confidence: 99%